2014
DOI: 10.1111/vcp.12140
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic findings from a benign giant cell tumor of the tendon sheath in a dog

Abstract: A 6-year-old male neutered Australian Shepherd dog was presented for evaluation of a subcutaneous mass on the plantar aspect of the proximal left metatarsus. Fine-needle aspirate smears contained numerous plump spindle cells and large multinucleated cells amongst a considerable amount of pink extracellular matrix. Histopathologic diagnosis of the tissue obtained during initial biopsy and eventual surgical cytoreduction of the mass was a benign giant cell tumor of the tendon sheath (GCTTS). Immunohistochemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, when reported, it is more frequently observed in large breed adult dogs and often shows a unilateral presentation similar to that observed in this study; although, a few cases of bilateral presentations have also been reported (MARTI, 1997;CAMPBELL et al, 2014;DEMPSEY et al, 2018). PVNTS affecting the radiocarpal-metacarpal, scapular-humeral, and tibiofibulo-patellar joints, and the sheath of the metatarsal tendon has been reported in dogs; however, involvement of the tarso-tibio-fibular joint has not been previously reported (YOUNG & HUDACEK, 1954;MARTI, 1997;HANSON, 1998;CAMPBELL et al, 2014;DEMPSEY et al, 2018). In this case, the lesion was localized, involving the deep digital flexor tendon in intra-articular presentation and extending to the extra articular region surrounding the tendon.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…However, when reported, it is more frequently observed in large breed adult dogs and often shows a unilateral presentation similar to that observed in this study; although, a few cases of bilateral presentations have also been reported (MARTI, 1997;CAMPBELL et al, 2014;DEMPSEY et al, 2018). PVNTS affecting the radiocarpal-metacarpal, scapular-humeral, and tibiofibulo-patellar joints, and the sheath of the metatarsal tendon has been reported in dogs; however, involvement of the tarso-tibio-fibular joint has not been previously reported (YOUNG & HUDACEK, 1954;MARTI, 1997;HANSON, 1998;CAMPBELL et al, 2014;DEMPSEY et al, 2018). In this case, the lesion was localized, involving the deep digital flexor tendon in intra-articular presentation and extending to the extra articular region surrounding the tendon.…”
supporting
confidence: 87%
“…in the histological section are reactive macrophages that present receptors for such cytokines (CSF1-R) (WEST et al, 2006). Giant cell tumors of the tendon sheath have been regarded as a rare disease in some studies in veterinary medicine, and there is only one recent report in dogs (CAMPBELL et al, 2014). The characteristic cystic appearance of the mass in this study should be distinguished from that of a synovial cyst, which has similar characteristics.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Giant cell tumor of soft parts is a rare neoplasm, reported in several domestic species, including dogs, cats, and horses. 1,2 In the equine species, it represents one percent of all cutaneous neoplasms. 3 It affects mostly adult animals, with the majority of horses over the age of 10 years.…”
Section: Discussionmentioning
confidence: 99%